The Effect Of Annealing On The Crystal Structure Of The Silicon Surface Doped With Nickel Ions (Texas Journal of Engineering and Technology, 2025)
The paper presents the results of a study of the distribution profiles of implanted nickel atoms in silicon as a function of the radiation dose and the annealing temperature using the Rutherford backscattering spectrometry technique (RBS). The effects of thermal annealing on the distribution of nickel and in particular oxygen are studied. It has been proven that under certain conditions of heat treatment and radiation doses, the so-called epitaxial silicides are formed on the surface of a single crystal, which can play the role of conductive layers or metallic coatings. The possibility of using the RBS technique for analyzing both the concentration distribution of doping impurities and the interaction of impurities is argued.